Implementation and Administrative Framework of the Inclusive Education in the Context of the European Integration Process - KULISH, Anatoliy N.; HARUST, Yuriy V.; REZNIK, Oleg N.; UTKINA, Maryna S. (Journal of Advanced Research in Law and Economics; Vol 7 No 6 (2016): Vol 7, No 6(2016): JARLE, Volume VII, Issue 6(20), Fall 2016, 2017)
This paper presented consolidated information about Ukrainian education system in past and about the role of the Inclusive Education in the Context of the European Integration Process. An inclusive education is a system of the educational services, which are based on the principle of the enforcement of main right of children to education and the right to study according to place of residence. Conception of the development of the inclusive education was developed, which aimed to solve important issues as to ensuring of the right to the equal education for children with special educational needs. The positioning socially recognized mission to unite the social community by meeting the needs of society in the creation of conditions of equal access to education for all of its members. The characteristic of national and foreign legal acts showed, that the implementation of the inclusive education into national schools characterized by maximum involvement of the state to the systematic problem solving, but there are no strict mechanism of the given process realization.
Keywords: inclusive education; European integration process; Ukraine; educational space; teachers; children with special educational needs